Effect of ternary additions of Cu and Fe on the hot deformation behavior of NiTi shape memory alloy - A study using processing maps. (April 2021) - Nayan, Niraj; Singh, Gaurav; Murty, S.V.S. Narayana; Narayan, P. Ramesh; Mohan, M.; Venkitakrishnan, P.V.; Ramamurty, Upadrasta
Abstract: The addition of ternary alloying elements Cu and Fe on the hot workability of binary NiTi SMA is assessed using the processing maps approach. Uniaxial compression test data obtained in the temperature, T, range 800–1050 °C and strain rate, ε ˙, of 10 −3 – 10 +1 s −1 were utilized to construct power dissipation, instability and strain rate sensitivity maps at true strain, ε  = 0.5. These maps and complementary microstructural analyses of the deformed specimens were used to identify various deformation mechanisms operating in different T - ε ˙ regimes. Based on the processing maps, three stable domains for processing were identified with Domain-2 occurring at higher T and intermediate ε ˙ with power dissipation efficiency of 30–45% being the optimum for thermo-mechanical processing. The addition of Cu in NiTi SMA improves its hot workability through enlarging stable domains for processing whereas Fe addition shrinks it. Microstructural analysis indicates occurrence of dynamic recrystallization (DRX) in NiTi, NiTiFe and dynamic recovery (DRV) in NiTiCu as the dominating deformation mechanism in Domain-2. Sluggish DRX kinetics in NiTiCu SMA in Domain-2 is related to its higher deformation resistance and higher critical stress required for the onset of DRX vis-à-vis NiTi, NiTiFe SMAs. Instability maps corroborated through microstructural analysis showed instability in the form of flow localization. Highlights: The effect of ternary additions of Cu and Fe on the hot-deformation behavior and processing map of NiTi shape memory alloy was investigated. Cu addition in NiTi improves its hot workability in terms of expanding safe regime for processing while Fe addition shrinks it. Flow stress was modeled using Arrhenius type hyperbolic-sine function and compared with experimentally determined values. Microstructural instability in the form of flow localization was observed in the instability regions of the processing maps.